Norepinephrine alkaloids as antiplasmodial agents: Synthesis of syncarpamide and insight into the structure-activity relationships of its analogues as antiplasmodial agents - Aratikatla, Eswar K.; Valkute, Tushar R.; Puri, Sunil K.; Srivastava, Kumkum; Bhattacharya, Asish K. (European Journal of Medicinal Chemistry, 2017)
Syncarpamide 1, a norepinephrine alkaloid isolated from the leaves of Zanthoxylum syncarpum (Rutaceae) exhibited promising antiplasmodial activities against Plasmodium falciparum with reported IC50 values of 2.04 mu M (D6 clone), 3.06 mu M (W2 clone) and observed by us 3.90 mu M (3D7 clone) and 2.56 mu M (K1 clone). In continuation of our work on naturally occurring antimalarial compounds, synthesis of syncarpamide 1 and its enantiomer, (R)-2 using Sharpless asymmetric dihydroxylation as a key step has been accomplished. In order to study structure-activity-relationship (SAR) in detail, a library of 55 compounds (3-57), which are analogues/homologues of syncarpamide 1 were synthesized by varying the substituents on the aromatic ring, by changing the stereocentre at the C-7 and/or by varying the acid groups in the ester and/or amide side chain based on the natural product lead molecule and further assayed in vitro against 3D7 and K1 strains of P. falciparum to evaluate their antiplasmodial activities. In order to study the effect of position of functional groups on antiplasmodial activity profile, a regioisomer (S)-58 of syncarpamide 1 was synthesized however, it turned out to be inactive against both the strains. Two compounds, (S)-41 and its enantiomer, (R)-42 having 3,4,5-trimethoxy cinnamoyl groups as side chains showed better antiplasmodial activity with IC50 values of 3.16, 2.28 mu M (3D7) and 1.78, 2.07 mu M (I(1), respectively than the natural product, syncarpamide 1. Three compounds (S)-13, (S)-17, (S)-21 exhibited antiplasmodial activities with IC50 values of 6.39, 6.82, 6.41 mu M against 3D7 strain, 4.27, 7.26, 2.71 mu M against K1 strain and with CC50 values of 147.72, 153.0, >200 mu M respectively. The in vitro antiplasmodial activity data of synthesized library suggests that the electron density and possibility of resonance in both the ester and amide side chains increases the antiplasmodial activity as compared to the parent natural product 1: The natural product syncarpamide 1 and four analogues/homologues out of the synthesized library of 55, (S)-41, (R)-42, (S)-55 and (S)-57 were assayed in vivo assay against chioroquine-resistant P. yoelii (N-67) strain of Plasmodium. However, none of the five molecules, 1, (S)-41, (R)-42, (S)-55 and (S)-57 exhibited any promising in vivo antimalarial activity against P. yoelii (N-67) strain. Compounds 4, 6, 7 and 11 showed high cytotoxicities with CC50 values of 5.87, 5.08, 6.44 and 14.04 mu M, respectively. Compound 6 was found to be the most cytotoxic as compared to the standard drug, podophyllotoxin whereas compounds 4 and 7 showed comparable cytotoxicities to podophyllotoxin. (C) 2017 Elsevier Masson SAS. All rights reserved.